An unusual reason for complete atrioventricular block; Kearn Sayre Syndrome - (:unkn) unknown (My University, 2016)
0

Kearn sayre syndrome (KSS) is a rare disease with a typical onset before 20 years and characterized by triad of chronic progressive external ophthalmoplegia, retinitis pigmentosa and progressive cardiac conduction abnormalities. The most important prognostic factor in KSS patients is the involvement of heart characterized by progressive degeneration of the conduction system. In patients with KSS, early diagnosis of cardiac involvement is very important because complete atrioventricular (AV) block may develop and it can be cause of sudden cardiac death. Herein we report a patient with KSS who presented with syncope due to complete AV block
Keywords: Genel ve Dahili Tıp